1997
DOI: 10.1104/pp.114.3.871
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Modified Lignin in Transgenic Tobacco Plants in Which the Activity of 4-Coumarate:Coenzyme A Ligase Is Depressed

Abstract: Transgenic tobacco (Nicotiana tabacum 1.) plants in which the activity of 4-coumarate:coenzyme A ligase is very low contain a novel lignin in their xylem. Details of changes in hydroxycinnamic acids bound to cell walls and in the structure of the novel lignin were identified by base hydrolysis, alkaline nitrobenzene oxidation, pyrolysis-gas chromatography, and '3C-nuclear magnetic resonance analysis. In the brownish tissue of the transgenic plants, the levels of three hydroxycinnamic acids, p-coumaric, ferulic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 20 publications
(12 reference statements)
2
76
0
1
Order By: Relevance
“…Coloration of xylem or wood has been reported in transgenic plants or mutants with repression of other lignin pathway genes such as COMT, 4-coumarate: coenzyme A ligase, and cinnamyl alcohol dehydrogenase (Halpin et al, 1994;Atanassova et al, 1995;Doorsselaere et al, 1995;Campbell and Sederoff, 1996;Kajita et al, 1997;Ralph et al, 1997;Tsai et al, 1998). Xylem or wood in plants with repression of COMT or cinnamyl alcohol dehydrogenase often shows strong red coloration, which has been attributed to the accumulation of hydroxycinnamyl aldehydes (Halpin et al, 1994;Higuchi et al, 1994;Ralph et al, 1997;Stewart et al, 1997;Tsai et al, 1998).…”
Section: Coloration Of Wood With Repression Of Ccoaomtmentioning
confidence: 99%
See 1 more Smart Citation
“…Coloration of xylem or wood has been reported in transgenic plants or mutants with repression of other lignin pathway genes such as COMT, 4-coumarate: coenzyme A ligase, and cinnamyl alcohol dehydrogenase (Halpin et al, 1994;Atanassova et al, 1995;Doorsselaere et al, 1995;Campbell and Sederoff, 1996;Kajita et al, 1997;Ralph et al, 1997;Tsai et al, 1998). Xylem or wood in plants with repression of COMT or cinnamyl alcohol dehydrogenase often shows strong red coloration, which has been attributed to the accumulation of hydroxycinnamyl aldehydes (Halpin et al, 1994;Higuchi et al, 1994;Ralph et al, 1997;Stewart et al, 1997;Tsai et al, 1998).…”
Section: Coloration Of Wood With Repression Of Ccoaomtmentioning
confidence: 99%
“…Xylem or wood in plants with repression of COMT or cinnamyl alcohol dehydrogenase often shows strong red coloration, which has been attributed to the accumulation of hydroxycinnamyl aldehydes (Halpin et al, 1994;Higuchi et al, 1994;Ralph et al, 1997;Stewart et al, 1997;Tsai et al, 1998). In plants with repression of 4-coumarate-coenzyme A ligase, xylem displayed a brownish color, probably due to accumulation of hydroxycinnamic acids (Kajita et al, 1997). It is obvious that the coloration of wood with repression of CCoAOMT could not be caused by hydroxycinnamyl aldehydes because the CCoAOMT-mediated reaction is at the early step of the phenylpropanoid pathway.…”
Section: Coloration Of Wood With Repression Of Ccoaomtmentioning
confidence: 99%
“…Questions remain as to why certain species appear to possess multiple, apparently similar, 4CL isoforms, whereas others such as potato (Solanum tuberosum) and pine (Pinus taeda) do not (BeckerAndré et al, 1991;Voo et al, 1995;Zhang and Chiang, 1997). If the possibility is accepted that isoforms expressed in specialized tissues of certain species have specific and distinct roles, then it is also possible that those isoforms are more specialized and differ more strikingly and with greater consequences in vivo than would be concluded from the in vitro studies to date.Analysis of transgenic tobacco (Nicotiana tabacum) and aspen plants revealed strikingly unequal effects of 4CL down-regulation on in vivo utilization of its three most preferred substrates, PA, CA, and FA (Kajita et al, 1997;Hu et al, 1999 Article, publication date, and citation information can be found at www.plantphysiol.org/cgi …”
mentioning
confidence: 99%
“…Analysis of transgenic tobacco (Nicotiana tabacum) and aspen plants revealed strikingly unequal effects of 4CL down-regulation on in vivo utilization of its three most preferred substrates, PA, CA, and FA (Kajita et al, 1997;Hu et al, 1999 Article, publication date, and citation information can be found at www.plantphysiol.org/cgi…”
mentioning
confidence: 99%
“…Prese~~tly, it is difficult to anticipate the consequences of genetic manipulation of the biosynthetic pathways of lignin on growth, develop~ner~tal and morphogenetic behavior of pli~nts. Several attempts have bee11 made to genetically ma~lipulate lignin biosynthesis via the transge~~ic approi~cli (Sederoff et (I/., 1994;Atanasova et al, 1995;Doorsselaere et al, 1995;Kajita et al, 1997). In addition to co~~tributing to the strength of wood, lignin also plays a crucial role in the ability of wood to resist pathogen infection and rotting.…”
Section: Wood C111d Pulp Qttalitymentioning
confidence: 99%